Gedikli Höyük Kazıları Çanak Çömleğinin Mineralojik ve Petrografik Yöntem ile İncelenmesi - Alkım, Handan
Englische Zusammenfassung: The Mineralogical and Petrographical Analysis of the Ceramics of Gedikli Höyük.